INTEGRATING AGRICULTURAL TECHNOLOGY WITH ENVIRONMENTAL SUSTAINABILITY: INSIGHTS FROM YUNNAN PROVINCE - Thompson, Daniel (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
Yunnan's exceptional ecological environment, shaped by its diverse topography and climatic conditions, provides a unique advantage. The region's complex ecosystem serves as a habitat for a wide array of plant and animal species, culminating in the selection of Kunming as the host city for the COP15 conference in October 2021. Given the integral role of modern technology in agricultural development, this study explores the pivotal question of how to harmonize agricultural technology promotion with the ecological environment, mitigating its potential adverse impact. It also seeks to identify a path forward for agricultural technology promotion reform in Yunnan Province. This research addresses the critical need for aligning agricultural advancements with the preservation of Yunnan's distinctive ecological heritage.